2017
DOI: 10.2217/fon-2016-0389
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Prevent Peritoneal Carcinomatosis Arising from Colorectal Cancer

Abstract: In the last decades, cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy became a curative option for peritoneal metastases in selected patients, otherwise considered for palliative therapy alone. Better knowledge of physiopathology of peritoneal spread and identification of predictive factors for peritoneal relapse prompted specialized centers to investigate the role of a 'proactive approach' in order to early detect peritoneal metastasis. These encouraging data could justify an acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 92 publications
0
7
0
1
Order By: Relevance
“…Non-obstructed tumors should not be resected but treated by stomas or stents, although colonic stenting should be avoided in patient candidates for antiangiogenic agents because of higher rates of perforation reported[1]; (2) Always provide adequate biopsies of the primary tumor and/or peritoneal implants; (3) Describe the extension of the peritoneal disease using the peritoneal cancer index (PCI) score. If limited peritoneal disease is found, there is still a high recommendation to not perform surgical resection in the emergency context because it does not add a better free-disease survival and could hinder a better combined treatment modality[23,24].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Non-obstructed tumors should not be resected but treated by stomas or stents, although colonic stenting should be avoided in patient candidates for antiangiogenic agents because of higher rates of perforation reported[1]; (2) Always provide adequate biopsies of the primary tumor and/or peritoneal implants; (3) Describe the extension of the peritoneal disease using the peritoneal cancer index (PCI) score. If limited peritoneal disease is found, there is still a high recommendation to not perform surgical resection in the emergency context because it does not add a better free-disease survival and could hinder a better combined treatment modality[23,24].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In addition, a recent French study have suggested that the addition of Oxaliplatin-HIPEC on the top of cytoreductive surgery does not influence both overall survival and disease-free survival but suggest that HIPEC with Oxaliplatin may be beneficial for patients with a medium PCI. [11][12][13][14][15]27 Therefore, at the present time, the role of HIPEC in the treatment of PC is not clear, and long-term results have to be awaited to assess the role of prophylactic/ adjuvant HIPEC.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) has achieved median survival rates of up to 64 months; peritoneal cancer index (PCI) and complete surgical cytoreduction (CRS-0) are the two main predictors of prognosis with this strategy. [8][9][10][11][12][13][14][15] Nonetheless, CRS and HIPEC are not risk-free, with nonnegligible associated morbidity and mortality. 16,17 Numerous clinical, pathological, and biological factors have been studied to identify patients with the highest risk of having synchronous or developing metachronous PC and to be able to diagnose it early, while the PCI is still low, and have an impact on outcomes in this population.…”
mentioning
confidence: 99%
“…Prophylactic HIPEC to complete second-look surgery has been tested as an adjuvant treatment in colorectal cancer patients at risk of peritoneal recurrence. 8 Second-look exploration with prophylactic HIPEC in a selected group of patients with resected lowgrade appendiceal tumors at risk of peritoneal relapse has been proposed. [9][10][11] Laparoscopy could be the ideal means for a HIPEC delivery protocol to treat patients with LAMN at high risk of peritoneal failure.…”
Section: Introductionmentioning
confidence: 99%